The first detection of SARS-CoV-2 RNA in urban wastewater in Giza, Egypt - Mohamed N. F. Shaheen; Elmahdy M. Elmahdy; Yasser E. Shahein (IWA Publishing, 2022)
The new coronavirus (SARS-CoV-2) is a respiratory virus causing coronavirus disease (COVID-19). Individuals with COVID-19 can shed the viral genome in their feces, even if they do not have symptoms, and the virus can be detected in wastewater. The current study provides the first surveillance of SARS-CoV-2 RNA genome in the wastewater in Egypt. To study this aim, untreated influent (n = 48) and treated effluent (n = 48) samples were collected between January and December 2021 from the wastewater treatment plant in Giza. The viral RNA genome was determined by reverse transcription-polymerase chain reaction (RT-PCR) (S, E, and N target regions) and real-time quantitative reverse transcription-PCR (RT-qPCR) (N1 and N2 target regions). The RT-PCR assay failed to detect SARS-CoV-2 RNA in all samples analyzed, whereas RT-qPCR succeeded in the detection of N gene of SARS-CoV-2 in 62.5% of untreated influent samples. The RT-qPCR Ct values of those samples tested positive ranged from 19.9 to 30.1 with a mean of 23. The treated effluent samples were negative for viral RNA detected by both RT-PCR and RT-qPCR, indicating the efficiency of the sewage treatment plant in degrading SARS-CoV-2. Our preliminary findings provide evidence for the value of wastewater epidemiology approach for the surveillance of SARS-CoV-2 in the population to assist in the responses of public health to COVID-19 outbreak. HIGHLIGHTS SARS-CoV-2 was detected in 62.5% of untreated influent samples.; RT-qPCR was more sensitive than RT-PCR.; The RT-qPCR Ct values ranged from 19.9 to 30.1 with a mean of 23.; There was a positive correlation between the number of sewage samples tested positive for SARS-CoV-2 RNA and the daily count of new active COVID-19 cases.;